1998
DOI: 10.1046/j.1365-201x.1998.0303f.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in skeletal muscle: synthesis, distribution and functional importance

Abstract: Over the last two decades, nitric oxide (NO) has been established as a novel mediator of biological processes, ranging from vascular control to long-term memory, from tissue inflammation to penile erection. This paper reviews recent research which shows that NO and its derivatives also are synthesized within skeletal muscle and that NO derivatives influence various aspects of muscle function. Individual muscle fibres express one or both of the constitutive NO synthase (NOS) isoforms. Type I (neuronal) NOS is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
195
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(206 citation statements)
references
References 59 publications
8
195
0
1
Order By: Relevance
“…NO is a weak reducing agent, with a relatively long half‐life70 and reacts with O 2 to form nitric dioxide and superoxide to produce peroxynitrite 110. There are three different isoforms of NOS expressed in skeletal muscle; the neuronal NOS (nNOS or type I), the inducible NOS (iNOS or type II) and the endothelial NOS isoenzyme (eNOS or type III) 46, 111. nNOS, originally discovered in neuronal tissue, is expressed along the sarcolemma of skeletal muscle fibres and interacts with the dystrophin–glycoprotein complex via a linkage to α1‐syntrophin 112.…”
Section: Chemistry Of Reactive Oxygen and Nitrogen Species Produced Bmentioning
confidence: 99%
“…NO is a weak reducing agent, with a relatively long half‐life70 and reacts with O 2 to form nitric dioxide and superoxide to produce peroxynitrite 110. There are three different isoforms of NOS expressed in skeletal muscle; the neuronal NOS (nNOS or type I), the inducible NOS (iNOS or type II) and the endothelial NOS isoenzyme (eNOS or type III) 46, 111. nNOS, originally discovered in neuronal tissue, is expressed along the sarcolemma of skeletal muscle fibres and interacts with the dystrophin–glycoprotein complex via a linkage to α1‐syntrophin 112.…”
Section: Chemistry Of Reactive Oxygen and Nitrogen Species Produced Bmentioning
confidence: 99%
“…A possible explanation for this threshold might be a NO-dependent reduction in skeletal muscle force via modulation of excitation-contraction coupling. It has been reported that the opening of the Ca 2ϩ release channels of the sarcoplasmic reticulum (SR) is inhibited by NO (32,35) and highly related to NO availability (35). In addition, Ca 2ϩ transport (35), SR Ca 2ϩ -ATPase activity (18), and cytochrome c-oxidase inhibition (9) may be influenced by NO and contribute to a dose-dependent modulation of excitation-contraction coupling.…”
Section: Dose Response: Severe-intensity Exercisementioning
confidence: 99%
“…It has been reported that the opening of the Ca 2ϩ release channels of the sarcoplasmic reticulum (SR) is inhibited by NO (32,35) and highly related to NO availability (35). In addition, Ca 2ϩ transport (35), SR Ca 2ϩ -ATPase activity (18), and cytochrome c-oxidase inhibition (9) may be influenced by NO and contribute to a dose-dependent modulation of excitation-contraction coupling. Therefore, whereas an increase in NO bioavailability may result in a more efficient mitochondrial function (24) and changes to type II fiber contractility (17) and blood flow (14), it is possible that these positive effects may be offset by impairments of mitochondrial or contractile function at higher NO levels that might promote nitrative stress.…”
Section: Dose Response: Severe-intensity Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Biological activities of NO and ROS are strongly interdependent (28,43). They and their redox derivatives compete for the same metal centers and thiol groups on the target protein (1,43).…”
Section: Effects Of No On Isotonic Contractile and Fatigue Propertiesmentioning
confidence: 99%